Energy and Resource Security: Some Insights - Sharma, Monica; Das, Sanjana (Energy Economics Letters, 2021)
The import-export paradox emerges when countries, despite being rich in resources, are not willing to use their resources and in turn import them from other countries thus, depleting the other countries’ resources. As a case study, the mining sector in India provides evidence of the import-export paradox as despite being rich in minerals, India imports three times its own production of the same. The growing global demand of energy only puts more stress on this issue and thus it is crucial to address this paradox in order to achieve energy and resource security. One of the ways for doing this could be by establishing a resource bank that treats resources as capital and by doing so it ensures that the resources being used are also being replenished. Steps can also be taken at G20 level to develop a cooperative framework to address the same. At the Indian level, initiatives such as the International Solar Alliance can be strengthened by increased allocation of finances in order to build greater capacities.